2020
DOI: 10.1039/d0tc00086h
|View full text |Cite
|
Sign up to set email alerts
|

Water-responsive actuators based on the solution casted PVA/epoxidized-SBS two-way shape memory bilayer composite film

Abstract: Water-responsive actuators have been an increasing interest in various applications. In this work, water-responsive actuators based on bilayer composite film were prepared using commercialized PVA and SBS by a two-step...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Once again, when this 2D‐shaped flower was immersed in water, it was able to regain its 3D closed state. Thus, the shape can actuate between two shapes (2D shape (blooming state) and 3D shape (closed state)) simultaneously via the drying and wetting process 158 . Another example is the claw‐shaped actuator which was shown to grab a screw weighing 1.05 gm (25 times of itself) when immersed in the water for 10 min.…”
Section: Sbs‐based Two‐way Shape Memory Polymersmentioning
confidence: 99%
See 3 more Smart Citations
“…Once again, when this 2D‐shaped flower was immersed in water, it was able to regain its 3D closed state. Thus, the shape can actuate between two shapes (2D shape (blooming state) and 3D shape (closed state)) simultaneously via the drying and wetting process 158 . Another example is the claw‐shaped actuator which was shown to grab a screw weighing 1.05 gm (25 times of itself) when immersed in the water for 10 min.…”
Section: Sbs‐based Two‐way Shape Memory Polymersmentioning
confidence: 99%
“…The PVA/e‐SBS based (A) flower‐like and (B) claw‐like actuators that show two‐way shape memory property when during the drying and the wetting process, reprinted with permission from Reference 158, copyright Royal society of chemistry, 2020. PVA, poly(vinyl alcohol); SBS, styrene butadiene styrene…”
Section: Sbs‐based Two‐way Shape Memory Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…Water not only had a driving function but also reduced the moduli of the matrix and hinge films because of the solvent effect. [32][33][34] Dynamic mechanical analysis (DMA) of the matrix and hinge films was conducted in air and water. It was found that the moduli of the matrix and hinge films decreased in water (Figure S6, Supporting Information).…”
Section: Control Mechanism In Shape-programming Processmentioning
confidence: 99%